Does assisted reproductive therapy (ART) increase the risk of neonatal unit admission or mortality for dichorionic diamniotic (DCDA) twins?. (7th June 2011) - Mullins, E; Cartwright, R; Denton, J; Kumar, S
Abstract : Introduction: Double embryo transfer is used in a majority of in vitro fertilization and ICSI treatment cycles in the UK, and commonly results in DCDA twin pregnancies. Compared to spontaneous conception, assisted reproductive therapy (ART) has been associated with poorer outcomes in singleton pregnancies.1 Comparative outcomes for DCDA pregnancies have not been clearly defined.2 Design: Cross-sectional study, using record linkage between our institutional maternity database, and the Twins & Multiple Births Foundation database. Methods: Data on ART, parity, maternal age, inter-twin weight discordance, birthweight, gestation at delivery, mode of delivery, stillbirth/IUD, neonatal unit (NNU) admission, neonatal death and infant death were obtained. Fetal, neonatal and infant mortality were grouped into a composite mortality outcome. Factors were tested in univariate analyses, and multivariate models were constructed using backward stepwise logistic regression in SPSS v17. Results: Data for 1174 pairs of DCDA twins were available over the period 1994–2008, with 268 (22.8%) resulting from ART. Neonatal admission Significant risks for NNU admission in univariate analysis included ART (p=0.026), delivery gestation, birthweight and weight discordance (all p<0.001). After adjustment in multivariate regression only gestation (OR 0.87/week, p=0.001) and birthweight (OR 0.325/kg p<0.001) remained significant. Composite mortality gestation, weight discordance, birthweight and mode of delivery were the only significant risks for mortality in univariate analysis (all p<0.001). Conclusion: In this large study of DCDA pregnancies, ART is identified as a risk factor for NNU admission. This effect is accounted for by increased rates of premature delivery and lower birthweight. ART has no effect on composite mortality.